2016
DOI: 10.1093/gji/ggw158
|View full text |Cite
|
Sign up to set email alerts
|

Seismotectonics and rupture process of theMW 7.1 2011 Van reverse-faulting earthquake, eastern Turkey, and implications for hazard in regions of distributed shortening

Abstract: S U M M A R YThe 2011 October 23 M W 7.1 Van earthquake in eastern Turkey caused ∼600 deaths and caused widespread damage and economic loss. The seismogenic rupture was restricted to 10-25 km in depth, but aseismic surface creep, coincident with outcrop fault exposures, was observed in the hours to months after the earthquake. We combine observations from radar interferometry, seismology, geomorphology and Quaternary dating to investigate the geological slip rate and seismotectonic context of the Van earthquak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 72 publications
(126 reference statements)
1
24
0
Order By: Relevance
“…Our study, along with the results of Copley (2014), Copley and Reynolds (2014), and Mackenzie et al (2016), shows that it is not always valid to assume that fold growth above blind reverse faults is coseismic or that it is appropriate to model it as an elastic dislocation. Even in cases where folds and coseismic uplift have been seen to match topography, such as at the Coalinga anticline, Stein and Ekström (1992) reported that a modest fraction of the folding was postseismic, so at best modeling all fold growth as coseismic is likely to overestimate the coseismic moment release rate.…”
Section: Timing Of Topographic Growthmentioning
confidence: 77%
See 1 more Smart Citation
“…Our study, along with the results of Copley (2014), Copley and Reynolds (2014), and Mackenzie et al (2016), shows that it is not always valid to assume that fold growth above blind reverse faults is coseismic or that it is appropriate to model it as an elastic dislocation. Even in cases where folds and coseismic uplift have been seen to match topography, such as at the Coalinga anticline, Stein and Ekström (1992) reported that a modest fraction of the folding was postseismic, so at best modeling all fold growth as coseismic is likely to overestimate the coseismic moment release rate.…”
Section: Timing Of Topographic Growthmentioning
confidence: 77%
“…The observations presented above allow us to place some constraints on the mechanisms controlling topographic growth at the northern Tibetan range front and its timing within the seismic cycle. Recent work on reverse faults has attributed topographic growth to various mechanisms depending on setting, including: coseismic slip (Le Béon et al, 2014;Stein & Ekström, 1992), postseismic afterslip on a single fault (Copley, 2014;Elliott et al, 2015Elliott et al, , 2016Stein and Ekström, 1992;Zhou et al, 2016), afterslip on multiple faults (Copley & Reynolds, 2014;Mackenzie et al, 2016) and slip on faults or sections of fault that play an apparently minor part in the region's seismic activity (Mackenzie et al, 2016;Melnick, 2016;Whipple et al, 2016).…”
Section: Timing Of Topographic Growthmentioning
confidence: 99%
“…We analyzed recent and past Google Earth imagery (1984–2017; DigitalGlobe–Landsat/Copernicus, Cnes/SPOT), the SPOT6 data, and declassified Corona satellite imagery (~2 m resolution) from the 1960s. The latter has the advantage of covering a time at which some tectonic features were not yet obliterated by urban development and infrastructure projects (Mackenzie et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The North and South Rey scarps are dotted due to uncertainty about whether they are formed by faulting. Talebian et al 2004;Walker 2006;Walker et al 2010Walker et al , 2013Copley 2014;Copley & Jolivet 2016;Mackenzie et al 2016). To examine the geomorphology we combine an interpretation of the landscape from old aerial photographs with an analysis of a high-resolution digital elevation model (DEM) that we generate from sub-metre stereo satellite imagery.…”
Section: Introductionmentioning
confidence: 99%